A survey of emergency medicine physicians’ knowledge, attitude, and practice towards esophagogastric variceal bleeding - Zhenzhen Gao; Yusong Gao; Shuai Ma; Tianpeng Zhang; Junyuan Wu; Shubin Guo; Xue Mei (International Journal of Emergency Medicine)
Abstract Background Esophageal-gastric variceal bleeding (EVB) is one of the leading causes of mortality in patients with cirrhotic portal hypertension. Rapid, accurate, and effective emergency care is crucial for successful patient outcomes. Aims This study aims to evaluate the knowledge, attitudes, and practices of Chinese emergency physicians regarding EVB, with the goal of improving the diagnosis and treatment of gastrointestinal bleeding in emergency settings. Methods A self-designed questionnaire based on clinical guidelines was developed to assess EVB knowledge, attitudes, and practices of Chinese emergency physicians in treating EVB. An online survey was conducted among emergency physicians nationwide. Data were analyzed using descriptive statistics and correlation analysis. Results The knowledge score for EVB was 11.2 ± 3.5 (total score was 22), indicating a relatively low level of understanding. Statistically significant differences in knowledge scores were observed across hospital grades, educational backgrounds, years of experience, professional titles, and participation in relevant training programs (P < 0.05). The mean attitude score for EVB was above 4 (total score was 5), reflecting a generally positive attitude among physicians. In terms of practices, the score for treatment behavior of EVB was 2.7 ± 1.2, and behavior was positively correlated with knowledge and attitude (P < 0.05). Conclusion Chinese emergency physicians demonstrate a low level of knowledge about EVB treatment, although their attitudes remain positive. Their clinical practices in EVB management are also insufficient. Enhancing education on EVB and standardizing treatment protocols are necessary to improve patient outcomes.